INDEK KEBAHAGIAAN DAN KEJADIAN PENYAKIT TIDAK MENULAR PADA GURU MADRASAH TSANAWIYAH - Yudha Laga Hadi Kusuma; Dwiharini Puspitaningsih (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
The happiness index of the Indonesian people has increased, on the other hand, the incidence of non-communicable diseases in the community has also increased. A person's happiness index has a contribution to a person's lifestyle, which later this lifestyle also has a contribution to the incidence of non-communicable diseases. This study wanted to know the index of happiness and symptoms of non-communicable diseases that exist in Madrasah Tsanawiyah teachers. This study used a descriptive research design involving 40 respondents from Madrasah Tsanawiyah teachers. The sampling technique used was consecutive sampling, with a study time of 2 days in March 2022. From the results of the study, it was found that the happiness index of teachers was quite happy at 62.2% and teachers who had normal blood pressure were 64.9%. The results of the analysis of the rank spearmen Rho about the relationship between the happiness index and blood pressure showed that the happiness index was significantly related to blood pressure with a p value of 0.000 and a large correlation of 0.681. The results of this study are expected to be used as a reference that happiness can contribute to a person's health status.